Subacute myoclonic measles encephalitis – An opportunistic HIV-associated infection - Ene, Luminita; Duiculescu, Dan; Radoi, Roxana; Lazar, Mihaela; Tardei, Gratiela; Ungureanu, Eugenia; Ruta, Simona; Vinters, Harry V.; Letendre, Scott; Grant, Igor; Ellis, Ronald J.; Achim, Cristian L. (Frontiers in Cellular Neuroscience, 2023)
Introduction: An unusual cluster of myoclonic epilepsy was observed in a Romanian pediatric HIV cohort concurrent with measles outbreaks. We describe this particular form of subacute measles encephalitis (SME) in a group of HIV-infected children and adolescents with severe immunosuppression. Methods: This is a single-center study, starting in 1997 and covering 4 measles outbreaks in Romania Presumptive diagnosis of subacute myoclonic measles encephalitis (SMME) was based on: 1) epidemiological data, previous measles episode or presumed contact with measles virus (MV), 2) clinical presentation with initial localized myoclonic jerks with rapid extension and subsequent motor deficit with preserved mental status, and 3) neuroimaging studies revealing cortical gray matter lesions. Definitive diagnosis was based on neuropathological exam and immunohistochemistry of brain tissues, and measles RNA detection in the cerebrospinal fluid (CSF). Results: Thirty-six patients were diagnosed with a particular form of SME during consecutive measles outbreaks in Romania: 1996-1998 (22); 2005-2008 (12); 2010-2011 (1) and 2016-2018 (1). Most children were born in the late 80s and had parenterally acquired HIV infection in early childhood. Before the episode of SMME 11 patients had confirmed measles, while the rest, without typical rash, had a respiratory tract infection and/or presumed previous measles contact. In all patients, the clinical onset was sudden, with unilateral myoclonus. MRI findings revealed mainly focal cortical gray matter lesions. Neurologic symptoms progressed rapidly to coma and death in most patients. Three patients survived SMME, they had higher CD4 count at onset, slower progression of neurological symptoms, and benefit of immune recovery with cART. Immunocytochemistry studies revealed MV in the brain with a pattern suggesting an ascending viral neural infection. MV was isolated from CSF in 7 out of 8 patients. Sequence analysis of MV RNA from both nasopharyngeal swab and CSF was available for one patient with similar N-450 strain characteristics. Conclusions: During an outbreak of measles, neurological manifestations, especially myoclonus in immunosuppressed patients, can be related to measles even in the absence of an acute episode. This particular form of subacute myoclonic measles encephalitis is an opportunistic fatal disease. Immune recovery due to effective antiretroviral treatment might increase survival.